Case report recurrent painful ophthalmoplegic neuropathy - Magalhães, Luciana Zelante Ambiel (2022)
Recurrent Painful Ophthalmoplegic Neuropathy (RPON) is a rare condition, previously known as Ophthalmoplegic Migraine, it is characterized by headache ipsilateral to paresis of the III, IV or VI cranial nerve, usually affects children or young adults. This is a report of a case of RPON in a 16-year-old woman treated at the Hospital do Servidor Público Estadual de São Paulo.